Easter Lily - (:unkn) unknown (My University, 2009)
An Easter greeting card of hand painted flower arrangement of white 'Easter lilies' or Calla lilies and Eucharist lilies. To Archie From Marie is written on the front of the postcard. Addressed to Mr. Archie Johnson, Baraboo, Wisconsin. Affixed to the postcard is a US 1 cent stamp. Postcard no. 7 in the series.
Colour: Hand painted; Style: Portrait; Other: Bordered, Divided
Keywords: Postcards; Flower arrangement; Lilies; Easter lily; Easter